أثر عقد الزوجية على ملكية المرأة - فتيحة مكحل; سامية بف حمزة; د/حفصي عباس (جامعة عمار ثليجي الاغواط, 2023)
الممخص كسمت ىذه الد ا رسة بعنكاف : أثر عقد الزكجية عمى ممكية الم أ رة في الفقو الإسلبمي د ا رسة تأصيمية ككاف مف – – أىدافيا التأصيؿ لي قضية مف قضايا الم أ رة الميمة ،التي كثر الجداؿ حكليا في العصر الحديث فكانت الإشكالية الرئيسية : ما مدل تأثير عقد الزكجية عمى ممكية الم أ رة ؟ كماىكا مسنده مف نصكص القرآف كالسنة ؟ عالجنا ىذه القضية في مقدمة كفصميف كخاتمة ، تطرقنا في الفصؿ الأكؿ إلى مفيك الذمة المالية كعمؿ الم أ رة ، تعرضنا لي أ ا رء العمماء كأدلتي في القضية ، أما الفصؿ الثاني فقد خصصناه إلى المصادر المالية لمزكجة قبؿ كبعد الزكاج كأىمية الم أ رة كاب ا رز الأىمية الكاممة لتصرفات الإقتصادية مف حيث جكاز التممؾ كالتصرؼ باليبة كالكصية كالبيع كغير ذلؾ في إطار قكاعد كأحكا الشريعة الإسلبمية ، كخاتمة تضمنت أى النتائج منيا أف الزكجة ليا ذمة مالية مستقمة كليا الحؽ التصرؼ فييا ، فيك أمر مقرر مادامت رشيدة . كأخي ا ر نسأؿ ا﵀ تعالى أف نككف قد كفقنا في عرضنا ليذه الرسالة كأف نككف قد أكفينا المكضكع حقو كمستحقو ، كما نسأؿ ا﵀ تعالى التكفيؽ كالسداد كالأجر كالثكاب كأخر دعكنا أف الحمد ﵀ رب العالميف ك كالصلبة كالسلب عمى سيد المرسميف سيدنا محمد بف عبد ا﵀ كعمى ألو كصحبو كمف إختط سبيمو كمنيجو إلى يك يمقاه. الكممات المفتاحية : الذمة المالية ، اثار عقد الزكاج. Abstract This study was entitled: The Impact of the Marriage Contract on Women's Ownership in Islamic Jurisprudence - A Foundational Study - One of its objectives was to root for me one of the important women's issues، about which there was much controversy in the modern era. The main problem was: What is the extent of the impact of the marriage contract on women's ownership? What is its chain of transmission from the texts of the Qur’an and Sunnah? We dealt with this issue in an introduction، two chapters، and a conclusion. In the first chapter، we dealt with the concept of financial responsibility and women’s work. We presented to me the opinions of scholars and their evidence in the case. As for the second chapter، we devoted it to the wife’s financial resources before and after marriage، the woman’s capacity، and highlighting the full capacity of the economic actions in terms of the permissibility of ownership. Disposing of a gift، will، sale، and so on within the framework of the rules and provisions of Islamic law، and a conclusion that included the most important results، including that the wife has an independent financial liability and has the right to dispose of it، so it is an established matter as long as she is rational. Finally، we ask God Almighty that we have succeeded in our presentation of this message and that we have fulfilled the topic in its right and deserved، as we ask God Almighty for success، repayment، reward and reward. And lastly we prayed that praise be to God، Lord of the worlds، and prayers and peace be upon the master of the messengers، our master Muhammad bin Abdullah and his family and companions and those Plan his path and method until the day he meets him. Keywords: financial disclosure، effects of the marriage contract.